Effects of Chemical Reactions on Unsteady Free Convective and Mass Transfer Flow from a Vertical Cone with Heat Generation/Absorption in the Presence of VWT/VWC. (24th July 2014) - Pullepu, Bapuji; Sambath, P.; Viswanathan, K. K.
Abstract : A mathematical model for the effects of chemical reaction and heat generation/absorption on unsteady laminar free convective flow with heat and mass transfer over an incompressible viscous fluid past a vertical permeable cone with nonuniform surface temperature T w ' ( x ) = T ∞ ' + a x n and concentration C w ' ( x ) = C ∞ ' + b x m is considered here. The dimensionless governing boundary layer equations of the flow that are transient, coupled, and nonlinear partial differential equations are solved by an efficient, accurate, and unconditionally stable finite difference scheme of Crank-Nicholson type. The velocity, temperature, and concentration profiles have been studied for various parameters, namely, chemical reaction parameter λ, the heat generation and absorption parameter Δ, Schmidt number Sc, Prandtl number Pr, buoyancy ratio parameter N, surface temperature power law exponent n, and surface concentration power law exponent m . The local as well as average skin friction, Nusselt number, and Sherwood number are discussed and analyzed graphically. The present results are compared with available results in open literature and are found to be in excellent agreement.